Changes in medical student attitudes as they progress through a medical course. Issue 2 (April 1998) - Price, J; Price, D; Williams, G; Hoffenberg, R
Abstract : OBJECTIVES: To explore the way ethical principles develop during a medical education course for three groups of medical students--in their first year, at the beginning of their penultimate (fifth) year and towards the end of their final (sixth) year. DESIGN: Survey questionnaire administered to medical students in their first, fifth and final (sixth) year. SETTING: A large medical school in Queensland, Australia. SURVEY SAMPLE: Approximately half the students in each of three years (first, fifth and sixth) provided data on a voluntary basis, a total of 385 students. RESULTS: At the point of entry, minor differences were found between medical students and first year law and psychology students. More striking were differences between male and female medical students, suggesting early socialization had a substantial impact here. CONCLUSIONS: Results indicate that substantial changes in attitude have developed by the beginning of fifth year with little change thereafter. Gender difference persisted. Some difference in ethical attitudes were found when groups of different ethnic backgrounds were compared. The impact of a move to a graduate medical course, which gives high priority to ethics within a professional development domain, can now be evaluated.